Constitutional safeguard for dalits -It Is an era started to treat SC,STs as human being - *Dr. Vishnuvardhan, (International Journal of Scientific Research and Management (IJSRM), 2025)
The Indian Constitution provides fundamental rights to its all citizens to treat equally in spite ofreligion, race, caste, sex, language and place of birth. Dalits are the downtrodden part of our society. From the time immortal they have been treated differently in the society. To protect these group of people and to achieve the goals of the Constitution and to fulfil the dreams of welfare state, provisions for the safe guard of dalits have been incorporated in the Constitution in its various Articles. The development of any nations depends on the overall development of the people. Dailts are the important part of our nation and the protection is very important. The important tool for the protection of dailts is the Constitution of India.